THERMOKINETICS OF META- AND ORTA-XYLENE ADSORPTION IN ZEOLITE Cu2+ZSM-5 - Yunusova R.G, Bakhronov Kh.N (Confrencea, 2022)
Among the aromatic hydrocarbons, benzene, toluene and p-xylene are the most easily adsorbed on ZSM-5 type zeolites (all of them have a kinetic diameter of 0.58 nm). The studies of the adsorption of benzene, toluene, and paraxylene in silicalite are the subject of works